Early Imaging and Molecular Changes with Neoadjuvant Bevacizumab in Stage II/III Breast Cancer - López-Vega, José Manuel (Cancers (Basel), 2021)
SIMPLE SUMMARY: New blood vessel formation (angiogenesis) has a crucial role in tumour growth and spread. Bevacizumab is an anticancer therapy that targets angiogenesis by inhibiting the vascular endothelial growth factor (VEGF) and is approved for the treatment of metastatic breast cancer. However, there are no validated methods for predicting which patients will respond to bevacizumab, although some have investigated whether a response can be predicted by using scanning (imaging) techniques that study tumour blood vessels or by using the levels of VEGF markers before treatment. In this study, we used a combination of imaging techniques and VEGF marker levels to show that bevacizumab caused structural and functional changes in the blood vessels of breast tumours and substantially slowed tumour growth. The increasing availability and refinement of imaging technology can help to identify biomarkers that will be able to predict which patients with breast cancer are most likely to respond to bevacizumab. ABSTRACT: This prospective, phase II study evaluated novel biomarkers as predictors of response to bevacizumab in patients with breast cancer (BC), using serial imaging methods and gene expression analysis. Patients with primary stage II/III BC received bevacizumab 15 mg/kg (cycle 1; C1), then four cycles of neoadjuvant docetaxel doxorubicin, and bevacizumab every 3 weeks (C2–C5). Tumour proliferation and hypoxic status were evaluated using (18)F-fluoro-3′-deoxy-3′-L-fluorothymidine (FLT)- and (18)F-fluoromisonidazole (FMISO)-positron emission tomography (PET) at baseline, and during C1 and C5. Pre- and post-bevacizumab vascular changes were evaluated using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Molecular biomarkers were assessed using microarray analysis. A total of 70 patients were assessed for treatment efficacy. Significant decreases from baseline in tumour proliferation (FLT-PET), vascularity, and perfusion (DCE-MRI) were observed during C1 (p ≤ 0.001), independent of tumour subtype. Bevacizumab treatment did not affect hypoxic tumour status (FMISO-PET). Significant changes in the expression of 28 genes were observed after C1. Changes in vascular endothelial growth factor receptor (VEGFR)-2p levels were observed in 65 patients, with a > 20% decrease in VEGFR-2p observed in 13/65. Serial imaging techniques and molecular gene profiling identified several potentially predictive biomarkers that may predict response to neoadjuvant bevacizumab therapy in BC patients.